Increasing Awareness of Soft-Tissue Sarcoma: Podcast of a Patient–HCP Discussion - Gillian Faskin; Sam Hackett (Oncology and Therapy)
Abstract Soft-tissue sarcoma is a rare cancer, making up less than 1% of new cancer diagnoses. They comprise tumours of the connective tissue, and as such can arise in any part of the body and can mimic other conditions. In addition, there are over 80 subtypes of sarcoma which, combined with the fact that most general practitioners may only see one case of sarcoma in their working lifetime, makes them difficult to diagnose. Sarcoma UK’s national sarcoma survey (2020) showed that 23% of patients started their treatment for an incorrect diagnosis before receiving their correct sarcoma diagnosis. Given the rarity of sarcoma, it is critical that patients are seen by a specialised sarcoma service as soon as possible so that all appropriate treatment pathways can be made available. However, 13% of patients never get to see a specialist multidisciplinary team. It is clear that many challenges remain in identifying patients with sarcoma and ensuring that they receive the best care possible. In this podcast a patient with sarcoma and a specialist sarcoma nurse discuss the patient’s journey from initial diagnosis through to treatment and recovery. They will also discuss the physiological, emotional and mental impact that sarcoma had, as well as the critical role of the cancer nurse specialist within the treatment plan, alongside a patient support group. Listeners to the podcast will gain a better understanding of the challenges in diagnosing soft-tissue sarcoma, the tools that are already available to assist physicians in diagnosis, and the importance of providing patients with clear information throughout the treatment journey. Podcast Audio (MP4 804666 KB)